Application of Geospatial Survey Technologies to Support Engineering and Industrial Development - Megan L. Hart Megan L. Hart; Daniel J. Kim; Priya N. Iyer Priya N. Iyer (Kalam Practica Media, 2025)
The rapid development of engineering and industrial projects has significantly increased the demand for accurate, efficient, and reliable spatial data. Geospatial survey technologies play a critical role in providing foundational information required for planning, construction, monitoring, and evaluation of engineering activities. Conventional survey methods are increasingly complemented by advanced geospatial technologies such as Global Navigation Satellite System (GNSS), total station, unmanned aerial vehicle (UAV) photogrammetry, and geographic information systems (GIS). This study aims to analyze the application of geospatial survey technologies in supporting engineering and industrial development through a descriptive-analytical approach. The research synthesizes technical principles, operational performance, accuracy characteristics, and implementation challenges of commonly used geospatial survey instruments in engineering projects. Data were obtained from technical documentation, standards, and relevant empirical studies, which were then analyzed to evaluate the effectiveness of each technology in different engineering contexts. The results indicate that the integration of modern geospatial survey technologies enhances spatial accuracy, reduces operational time, and improves decision-making quality in industrial development projects. Technological adoption is influenced by factors such as operator competence, environmental conditions, and system interoperability. This study contributes to applied geospatial engineering literature by providing a structured evaluation of survey technologies and their practical implications for engineering and industrial applications.